2021
DOI: 10.1039/d0ta11270d
|View full text |Cite
|
Sign up to set email alerts
|

A pressure induced reversal to the 9R perovskite in Ba3MoNbO8.5

Abstract: Ba3MoNbO8.5 is an oxide ion conductor with an unconventional hybrid structure that is intermediate between the 9R-perovskite (A3B3O9) and the palmierite (A3B2O8) unit cell. The structure is highly disordered with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Similar trends have been reported in various related Ba 3 M ′ M ′′O 8.5 materials and have been associated with changes in the oxygen populations and to different occupation of the cation sites. Overall, our in situ neutron diffraction experiments and DFT calculations demonstrate that water is clearly responsible for the unusual variation of the crystal structures with temperature and a main driver of the cation and anion disorder exhibited by these cation deficient hexagonal derivatives. These results also confirm the intrinsic structural flexibility of these systems, as further highlighted by a recent variable pressure study on Ba 3 NbMoO 8.5 which revealed a low bulk modulus closer in magnitude to that of the halide perovskites . In cubic perovskite systems, any reduction in symmetry reduces the water solubility .…”
Section: Results and Discussionsupporting
confidence: 84%
“…Similar trends have been reported in various related Ba 3 M ′ M ′′O 8.5 materials and have been associated with changes in the oxygen populations and to different occupation of the cation sites. Overall, our in situ neutron diffraction experiments and DFT calculations demonstrate that water is clearly responsible for the unusual variation of the crystal structures with temperature and a main driver of the cation and anion disorder exhibited by these cation deficient hexagonal derivatives. These results also confirm the intrinsic structural flexibility of these systems, as further highlighted by a recent variable pressure study on Ba 3 NbMoO 8.5 which revealed a low bulk modulus closer in magnitude to that of the halide perovskites . In cubic perovskite systems, any reduction in symmetry reduces the water solubility .…”
Section: Results and Discussionsupporting
confidence: 84%
“…The ratio of tetrahedral to octahedral units varies greatly for the Ba 3 M′M″O 8.5 phases with Ba 3– x VMoO 8.5– x presenting the highest percentage of tetrahedra (∼86.8%) in the average structure at room temperature, followed by Ba 3 VWO 8.5 (∼66.2%), then Ba 3 NbMoO 8.5 (∼49.9%) with Ba 3 NbWO 8.5 displaying the lowest percentage (∼13.1%). ,, This ratio depends on the geometrical preference of the cations present, with V 5+ and Mo 6+ favoring tetrahedral geometry while Nb 5+ and W 6+ typically adopt octahedral geometry . A recent study investigating the effect of pressure on Ba 3 NbMoO 8.5 concluded that, as pressure is increased, the percentage of tetrahedra decreases, which results in greater distortion of the tetrahedral units . On the contrary, in Ba 3– x VMoO 8.5– x the geometry of the palmierite-like layer is predominantly tetrahedral, resulting in a much-reduced distortion of the tetrahedral units.…”
Section: Results and Discussionmentioning
confidence: 98%
“…21 A recent study investigating the effect of pressure on Ba 3 NbMoO 8.5 concluded that, as pressure is increased, the percentage of tetrahedra decreases, which results in greater distortion of the tetrahedral units. 36 On the contrary, in Ba 3−x VMoO 8.5−x the geometry of the palmierite-like layer is predominantly tetrahedral, resulting in a much-reduced distortion of the tetrahedral units. The occurrence of neighboring octahedral and tetrahedral units in Ba 3 M′M″O 8.5 is facilitated by local disruption of the oxygen sublattice.…”
Section: ■ Results and Discussionmentioning
confidence: 99%